Novel Cephalosporins in Septic Subjects and Severe Infections: Present Findings and Future Perspective - Corcione, Silvia; Lupia, Tommaso; De Rosa, Francesco Giuseppe (Frontiers in Medicine, 2021)
In past decade, cephalosporins have developed significantly, and data regarding novel cephalosporins (i.e., ceftobiprole, ceftaroline, ceftolozane/tazobactam, ceftazidime/avibactam, and cefiderocol) within septic and bacteremic subjects are rising. These compounds generally offer very promising in vitro microbiological susceptibility, although the variability among gram-negative and -positive strains of different cohorts is noticed in the literature. We require further pharmacological data to measure the best dose in order to prevent sub-therapeutic drug levels in critically ill patients. These new compounds in theory are the sparing solution in the Enterobacteriales infection group for different antimicrobial classes such as aminoglycosides notably within endovascular and GNB-bacteremias, as well as colistin and carbapenem-sparing strategies, favoring good safety profile molecules. Moreover, new cephalosporins are the basis for the actual indications to open up new and exciting prospects for serious infections in the future. In future, patients will be addressed with the desirable approach to sepsis and serious infections in terms of their clinical situation, inherent features of the host, the sensitivity profile, and local epidemiology, for which evidence of the use of new cephalosporin in the treatment of severe infections will fill the remaining gaps.